Simulasi Numeris Karakteristik Pembakaran CH4/CO2/Udara dan CH4/CO2/O2 pada Counterflow Premixed Burner - Wicaksono, Hangga; Sasongko, Mega Nur; Widhiyanuriyawan, Denny (Jurnal Rekayasa Mesin, 2017)
The high amount of CO2 produced in a conventional biogas reactor needs to be considered. A further analysis is needed in order to investigate the effect of CO2 addition especially in thermal and chemical kinetics aspect. This numerical study has been held to analyze the effect of CO2 in CH4/CO2/OÂ2 and CH4/CO2/Air premixed combustion. In this study one dimensional analisys in a counterflow burner has been performed. The volume fraction of CO2 used in this study was 0%-40% from CH4â€™s volume fraction, according to the amount of CO2 in general phenomenon. Based on the flammability limits data, the volume fraction of CH4 used was 5-61% in O2 environment and 5-15% in air environment. The results showed a decreasing temperature along with the increasing percentage of CO2 in each mixtures, but the effect was quite smaller especially in stoichiometric and lean mixture. CO2 could affects thermally (by absorbing heat due to its high Cp) and also made the production of unburnt fuel species such as CO relatively higher.